African Poverty at the Millennium : Causes, Complexities, and Challenges - White, Howard; Killick, Tony; Kayizzi-Mugerwa, Steve; Savane, Marie-Angelique (Washington, DC: World Bank, 2013)
The multifaceted nature of the poverty problem, and the widening gap between the levels of human well-being in Africa, compared with the other developing regions, are the central themes of this report. The key elements of poverty reduction strategies in the region are reviewed, pointing at the need for accelerated economic growth, if living standards are to improve in Africa. To this end, the report outlines the growth of African poverty, amid the variations between countries, which reflect regional differences, such as higher levels of infant/child mortality in West Africa, though this gap is narrowing, partly because of the higher HIV/AIDS prevalence in eastern, and southern Africa. It analyzes the causes of poverty, through the interaction of cause and effect, neglect, and policy implications, and examines economic stagnation as the cause of much poverty, through an overview of growth vs. distribution, the slow pace of growth in Africa, and the impact of growth as it affects poverty groups differently. However, it also points at the failure of both governments, and markets in reducing poverty, stating political systems do contribute to economic stagnation, whereas sustainable social indicators require not only growing incomes, but improved state service provision. The need for the donor community to redefine poverty reduction is imminent, and the report suggests more selective aid allocation, including debt relief, in accordance with government commitments to reducing poverty.